Factors Affecting Employee Performance at Puskesmas - Gunawan Gunawan; Fitrianingrum Fitrianingrum (Jurnal Indonesia Sosial Teknologi, 2025)
Puskesmas are health service facilities that organize public health efforts and first-level individual health efforts, by prioritizing promotive and preventive efforts, to achieve the highest degree of public health in their work area by the Regulation of the Minister of Health of the Republic of Indonesia Number 43 of 2019. The research design used in this study is a quantitative method with an associative approach. The results of the study were obtained 1) Workload affects employee performance at the Ngroto Health Center, where the value is determined by calculation using the SmartPLS software program version 4. obtained a value of 0.028 < 0.05 at a significance level of 5%. This indicates that H1 is acceptable; 2) remuneration affects employee performance at the Ngroto Health Center, where the value is determined by calculation using the SmartPLS software program version 4 obtained a value of 0.045 < 0.05 at a significance level of 5%. This indicates that H2 is acceptable; 3) Work motivation affects employee performance at the Ngroto Health Center, where the value is determined by calculation using the SmartPLS software program version 4. obtained a value of 0.012 < 0.05 at a significance level of 5%. This indicates that H3 is acceptable. The results of the study can be concluded as follows: 1) Workload affects employee performance at the Ngroto Health Center, where the value is determined by calculation using the SmartPLS software program version 4. obtained a value of 0.028 < 0.05 at a significance level of 5%. This indicates that H1 is acceptable. 2) Remuneration affects employee performance at the Ngroto Health Center, where the value is determined by calculation using the SmartPLS software program version 4 obtained a value of 0.045 < 0.05 at a significance level of 5%.